Epigenetic Mechanism and Therapeutic Implications of Atrial Fibrillation - Li, Dan; Nie, Jiali; Han, Yu; Ni, Li (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation (AF) is the most common arrhythmia attacking 1. 5–2.0% of general population worldwide. It has a significant impact on morbidity and mortality globally and its prevalence increases exponentially with age. Therapies like catheter ablation or conventional antiarrhythmic drugs have not provided effective solution to the recurrence for AF over the past decades. Over 100 genetic loci have been discovered to be associated with AF by Genome-wide association studies (GWAS) but none has led to a therapy. Recently potential involvement of epigenetics (DNA methylation, histone modification, and non-coding RNAs) in the initiation and maintenance of AF has partly emerged as proof-of-concept in the mechanism and management of AF. Here we reviewed the epigenetic features involved in AF pathophysiology and provided an update of their implications in AF therapy.